MENGEMBANGKAN KREATIVITAS ANAK MELALUI KEGIATAN MENGGAMBAR - Shokiyah, Nunuk Nur (Institut Seni Indoensia Surakarta, 2015)
This research aims to determine how to develop children’s creativitiesthrough drawing. This type of research is qualitative. The source of data in this study includes the children’s works, many literatures related to the research, documents, data collection techniques used in the study of literature,observation, and documentation. Results of the study are several ways to develop the children’s creativitiesthrough drawing. They include enriching children’s abilities in drawing, drawing freely, coloring by mixing a variety of medium, providing various facilities to draw, being creative every day,drawing while playing, drawing while storytelling, creative holidays, parental involvement. Some of the techniques describe efforts to develop the children’s creativitiesthrough drawing. This study emphasizes on the development of children’s creativities rather than emphasizing on the skill in drawing. Drawing activity gives more attention to the process than the results. It is important to make the children relaxwithout coercion from others when theyare drawing,so that the resulted image is very unique and naturally suitable to their expressive soul.Keywords: drawing, developing creativity